In search of Islamic view of justice on women testimony - Husni Mubarrak (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
The most current challenges faced by Moslem in terms of Islamic religious discourse are religiousinterpretation on gender equality on position men and women. Among long crucial debate related tothe issue is position of men and women in testimony, when the place of two women witnesses whichare conceived equal to one man. It seems an ambivalent takes place regarding Islamic religious interpretationwhen many verses mentioned in the Quran and some hadiths have declared explicitly the sameshared opportunity and capacity as well as mutual relation between men and women as vicegerents(khalifah) of God on the earth, meanwhile in the practice which inherited over centuries demonstratedinequality of men and women. This contrast, however, ultimately indicates a tension between Islamthat ethically egalitarian and historically determined. This article tries to seek an Islamic view of justice onwomen testimony by arguing the importance of contextualizing interpretation by revitalizing appropriatemaxim of Quran exegetes and up grading maqasid studies in order to find a more equal and justreligious interpretation on women in Islam.